International agreements and the plant genetics research community: A guide to practice - Marden, Emily; Hamilton, Ruaraidh S.; Halewood, Michael; McCouch, Susan (National Academy of Sciences, 2023)
Plant genetic resources (PGR), including collections held in national and international gene banks, provide access to a wide array of genetic diversity and are critical to genomics research, conservation efforts, and applied breeding. Yet, there is a general lack of awareness in the research community about the rules and treaties that govern the use of PGR, about access and benefit sharing obligations contained in international treaties and/or national laws, and about how best to comply with potentially applicable requirements. This article provides a brief history and overview of three key international agreements, namely the Convention on Biological Diversity, the Nagoya Protocol, and the International Treaty on Plant Genetic Resources for Food and Agriculture, which collectively address responsibilities and obligations related to the use of much of the world’s PGR. By highlighting the coverage and key considerations of each agreement, the article provides a guide for those who use PGR in plant genetics research to better understand when and how international agreements apply, and—where the rules are unclear—to suggest best practices for compliance with existing agreements.